2020
DOI: 10.5194/hess-24-5379-2020
|View full text |Cite
|
Sign up to set email alerts
|

Suitability of 17 gridded rainfall and temperature datasets for large-scale hydrological modelling in West Africa

Abstract: Abstract. This study evaluates the ability of different gridded rainfall datasets to plausibly represent the spatio-temporal patterns of multiple hydrological processes (i.e. streamflow, actual evaporation, soil moisture and terrestrial water storage) for large-scale hydrological modelling in the predominantly semi-arid Volta River basin (VRB) in West Africa. Seventeen precipitation products based essentially on gauge-corrected satellite data (TAMSAT, CHIRPS, ARC, RFE, MSWEP, GSMaP, PERSIANN-CDR, CMORPH-CRT, T… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(49 citation statements)
references
References 219 publications
(210 reference statements)
2
25
0
Order By: Relevance
“…They recommended the use of CHIRPS for flood and drought studies undertaken in Burkina Faso and Mozambique by Dembélé and Zwart (2016) and Toté et al (2015), respectively. Dembélé et al (2020b) also evaluated the suitability of 17 available gridded rainfall datasets for large-scale hydrological modelling in the Volta River basin and showed that CHIRPS is one of the best-performing datasets for streamflow simulation. The study also established that none of the rainfall datasets they tested consistently performed well in reproducing the spatiotemporal rainfall variability.…”
Section: Observation-based Driving Datamentioning
confidence: 99%
“…They recommended the use of CHIRPS for flood and drought studies undertaken in Burkina Faso and Mozambique by Dembélé and Zwart (2016) and Toté et al (2015), respectively. Dembélé et al (2020b) also evaluated the suitability of 17 available gridded rainfall datasets for large-scale hydrological modelling in the Volta River basin and showed that CHIRPS is one of the best-performing datasets for streamflow simulation. The study also established that none of the rainfall datasets they tested consistently performed well in reproducing the spatiotemporal rainfall variability.…”
Section: Observation-based Driving Datamentioning
confidence: 99%
“…spheric reanalysis for environmental studies. Several intercomparison studies have been done (e.g., Beck et al, 2017;Essou et al, 2017), including over Africa (Satgé et al, 2020;Dembélé et al, 2020). These studies outline a complex picture in which performance depends on scale, climate and data source and for which no dataset consistently outperforms all of the others.…”
Section: Discussionmentioning
confidence: 99%
“…The GRDC is arguably the most complete global discharge database providing free access to river discharge data (Fekete and Vörösmarty, 2007). The database provides streamflow records collected from 9213 stations across the globe, with an average temporal coverage of 42 years per station (Do et al, 2017). It is operated under the World Meteorological Organization (WMO) umbrella to provide broad hydrological data to support the scientific research community.…”
Section: Observed Streamflow Datamentioning
confidence: 99%
“…mHM has successfully been applied for several West African basins using a variety of forcing data and observational data as calibration targets [12,[30][31][32]. In our model setup for the Senegal River basin, elevation was retrieved from the Shuttle Radar Topographic Mission.…”
Section: Hydrological Modelmentioning
confidence: 99%
“…The robustness of the calibration experiments and the effectiveness of the proposed normalization strategy should be investigated in more detail. Ideally by means of an ensemble approach containing different precipitation forcing data sources as well as an ensemble of ET references [31,32].…”
Section: Calibration Strategymentioning
confidence: 99%